Candidate Germline Genetic Variants for Familial Colorectal Cancer Type X - Duarte, Teresa Patrícia da Silva Gil (2017)
Familial colorectal cancer type X (FCCTX) defines families that fulfill the Amsterdam criteria without evidence of defects in the DNA mismatch repair (MMR) genes and whose tumors do not present microsatellite instability. However, its genetic etiology remains unknown, therefore this study aimed to identify and evaluate novel variants and candidate genes that may play a role in FCCTX susceptibility. Based on a previous whole exome sequencing (WES) study in a FCCTX family, a bioinformatic analysis and a subsequent in silico and segregation studies were conducted to identify candidate genes and/or specific variants that may predispose for this syndrome. Since this analysis was already started, variants in 6 genes have already been identified to segregate with the disease. Therefore, the aim of this project was to continue this work by completing the selection of candidate variants and to characterize and try to clarify the role of these variants for FCCTX susceptibility. In order to elucidate the possible contribution of the corresponding genes for FCCTX, a mutational analysis was performed to search for germline mutations in index patients from FCCTX and FCCTX-like families. In addition, using the WES data, a copy number variation (CNV) analysis was also performed for the family subjected to WES, followed by a bioinformatic and in silico analysis to reveal amplicon deletions that may segregate with disease. It was also evaluated the involvement of the TPP2 gene, previously identified as a possible candidate gene for FCCTX in another family, in healthy and affected FCCTX patients, by mutational/splicing analysis, relative quantification by quantitative PCR and protein truncation test to assess resulting truncating proteins. The bioinformatic followed by in silico and segregation analysis of the variants obtained from WES, revealed 1 variant in the CACNA1S gene that segregated with the disease. Adding this variant to the already obtained, a total of 7 variants in different genes were found as possible contributors to FCCTX in this family. The segregation analysis also revealed the segregation of the previously identified MTMR3 and TAS1R1 variants in a patient from an older generation of the family. The CNV analysis revealed, after selective criteria, 22 amplicons of interest with a deletion scenario, for further segregation studies. The germline mutational analysis in a set of FCCTX and FCCTX-like families uncovered 2 and 3 potentially pathogenic variants for the MTMR3 and TAS1R1 genes, respectively. One of the variants found in MTMR3 was the same found in the WES analysis. Thus far no relevant variants were observed for LGR6 and DUSP12, however this analysis is not completed. The TPP2 study revealed the presence of non-described splicing isoforms. One of these isoforms exhibited a differential expression between healthy and affected individuals and the protein truncation test revealed that this alternative transcript gives rise to a truncated protein. In conclusion, the identification of more than one genetic variant appears to agree with the suggestion that FCCTX is a heterogeneous entity and the discovery of potentially pathogenic variants in MTMR3 and TAS1R1 reinforce their possible involvement in FCCTX. The alternative TPP2 transcript appears to be involved in the earlier stages of colorectal carcinogenesis